Disproportionate rise in serum CA 125 in case of budd chiari syndrome: an unusual presentation - Game, Prasad D.; Holay, Madhuri P.; Durgam, Satyanarayan; Kharkar, Sandeep (International Journal of Research in Medical Sciences, 2017)
Ca 125 is used as a diagnostic and prognostic biomarker for ovarian cancer. The level of CA 125 is also elevated in benign conditions like Budd Chiari syndrome, liver cirrhosis and heart failure. But very high level of CA 125 is rarely associated with benign conditions and this can mislead the physician. Here we present a case of budd chiari syndrome in postpartum period associated with very high level of CA 125 which is an unusual presentation.